TEACHERS' PERCEPTION ON ONLINE LEARNING OF ENGLISH FOREIGN LANGUAGE IN THE POST COVID-19 PANDEMIC - Pamungkas, Firdaus Ditya (Institut Agama Islam Negeri Ponorogo, 2023)
A global pandemic caused by Coronavirus or Covid-19 gave horrible impacts toward many important sectors, including education. This global crisis including Indonesia, forced educational institutions to switch their teaching methods into online teaching and learning for around two and a half years. In the post Covid-19 pandemic, the education was back to normal where schools and university accepted students to learn in the classes. Therefore, the use of online learning that was important during Covid-19 pandemic, might be useful to give variation in learning process in the post Covid-19 pandemic. This study was conducted to explore teachers’ perception on online learning of EFL in the post Covid-19 pandemic. The participants were 21 EFL teachers from university and secondary school in Indonesia. This study used a qualitative descriptive approach with online questionnaire. From the finding and result, it showed that teachers considered EFL online learning was still important because online learning provided flexible time in scope of teaching. Furthermore, the contents or materials of online learning could be saved on the internet for long time and could be seen or accessed again. In conclusion, EFL online still gave positive impact towards students and teachers in the post Covid-19 pandemic.Keyword: Post Covid-19 pandemic, EFL, perception, online learning